PARTS OF SPEECH PRACTICE USING TUSUK SATE MEDIA AND GREEN FINANCIAL EDUCATION: PRAKTIK PARTS OF SPEECH MENGGUNAKAN MEDIA TUSUK SATE DAN EDUKASI KEUANGAN HIJAU - Elda Yulia Ryandini; Rini Novianti; Eny Sulistyowati (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Learning English is still considered difficult by foreign learners, including understanding parts of speech in English grammar. It is considered important to learn because they relate to word order in forming correct sentences. In this learning, the regular use of conventional media is also necessary to increase teacher creativity and innovation, such as the use of Tusuk Sate (satay skewers) made from used goods. It is also related to the implementation of the green economy, namely green finance. Objective: This community service activity aims to provide an introduction to parts of speech using Tusuk Sate media and education on green financial practices. Method: This activity is a training on introducing English parts of speech using Tusuk Sate as a medium and educating 15 students of class XII on green financial practices using descriptive analyses. Results: Students can classify most English vocabulary according to parts of speech by 2.6%, and all students can give examples of green finance practices. Conclusion: From the English parts of speech practice activity using Tusuk Sate media and green financial practice education, all students were able to follow the activity process well and got a better understanding (post-test) compared to before (pre-test).